The clinical outcome of pazopanib treatment in Japanese patients with relapsed soft tissue sarcoma: A Japanese Musculoskeletal Oncology Group (JMOG) study. Issue 9 (11th March 2016) - Nakamura, Tomoki; Matsumine, Akihiko; Kawai, Akira; Araki, Nobuhito; Goto, Takahiro; Yonemoto, Tsukasa; Sugiura, Hideshi; Nishida, Yoshihiro; Hiraga, Hiroaki; Honoki, Kanya; Yasuda, Taketoshi; Boku, Shogen; et al.
Abstract : BACKGROUND: Because the efficacy and safety of pazopanib in Japanese patients with soft tissue sarcoma (STS) had not been evaluated previously in a large‐scale cohort, the authors investigated the efficacy and safety of pazopanib in 156 Japanese patients with relapsed STS. This was a retrospective study based on the collection of real‐life, postmarketing surveillance data. METHODS: Patients received pazopanib with the objective of treating local recurrence (n = 20), metastasis (n = 104), and both (n = 32). The patient median age was 53.8 years. The primary objective of this study was to clarify the efficacy of pazopanib for patients with STS. RESULTS: The median treatment duration was 28.7 weeks, and the average dose intensity of pazopanib was 609 mg. Adverse events occurred in 127 patients (81.4%). In addition to the main common toxicities, such as hypertension and liver disorder, pneumothorax (n = 11) and thrombocytopenia (n = 16) also were observed. The median progression‐free survival for all patients was 15.4 weeks. The median progression‐free survival for patients with leiomyosarcoma, synovial sarcoma, undifferentiated pleomorphic sarcoma, and liposarcoma was 18.6 weeks, 16.4 weeks, 15.3 weeks, and 8 weeks, respectively. The median survival for all patients was 11.2 months. The median survival for patients with leiomyosarcoma, synovial sarcoma, undifferentiated pleomorphic sarcoma, and liposarcoma was 20.1 months, 10.6 months, 9.5 months, and 7.3 months, respectively. CONCLUSIONS: There were apparent differences in the efficacy of pazopanib treatment among histologic types of STS. Pazopanib treatment is a new treatment option; however, adverse events like pneumothorax and thrombocytopenia, which did not occur frequently in the PALETTE study (pazopanib for metastatic soft‐tissue sarcoma), should be taken into consideration. Cancer 2016;122:1408‐16 . © 2016 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Abstract : Clinical outcomes of 156 Japanese patients with relapsed soft tissue sarcoma receive pazopanib treatment are investigated. There are apparent differences in the efficacy of pazopanib treatment among histologic types of soft tissue sarcoma.